Cassava - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1992)
Research activities related to biotechnology in cassava are indicated. A solid basis has been worked out for a upcoming project of the molecular mapping of the cassava genome. A basic set of polymorphic markers from cassava genomic libraries has been selected; the generation of the linkage map using these markers follows. Cassava has also been regenerated from secondary embryos forming an embryogenic calli stemming from apical meristems, which is the target issue for transformation expt. using Agrobacterium and the particle gun. Regarding cassava starch fermentation, work has been carried out on the characterization of microbial amylolytic activities involved in the process. Regarding the known adaptation mechanisms of cassava for dealing with climatic constraints such as drought and heat, without losing productivity, the possible compartmentalization of photosynthetic enzymes in the leaf by in situ hybridization, using labelled gene probes, is under study. A high degree of homology has been found between maize and cassava photosynthetic genes by hybridization techniques. A genomic cassava library is now being generated. (CIAT)